Macular hole surgery under retrobulbar local anesthesia increases visual acuity - Simanjuntak, Gilbert WS; Simanjuntak, Golda AM; Christine, Reinne Natali (Universa Medicina, 2017)
Background Macular hole surgery can be done under general or local anesthesia, and general anesthesia is still the standard procedure. The objective of this study was to investigate the results of macular hole surgery under local anesthesia. MethodsA retrospective study on medical records of patients who had undergone macular hole surgery under local anesthesia. Funduscopic examination of macular hole had been performed and all other diseases with deterioration of visual acuity eliminated. Surgery was performed under retrobulbar local anesthesia, using 2 ml of 2% lidocaine mixed with 3 ml bupivacaine in one syringe. Vitreous tamponade used 20% sulfur hexafluoride (SF6). Demographic and clinical characteristics, visual acuity before and after surgery, and improvements that occurred were assessed. Results No significant interruption occurred during surgery. Mean age of the patients was 53.89 ± 13.3 years (22-74 years), with mean duration of symptoms of 48.83 ± 100.51 weeks (1-560 weeks). The patients comprised 20 males (55.6%) and 16 females (44.4 5). There were improvements in visual acuity after surgery in 31 patients (86.1%), the rest (13.9%) had identical or lower visual acuity after surgery. A total of 20 patients (55.6%) had postoperative visual acuity of 6/18 or better. Initial mean preoperative visual acuity was 0.08 ± 0.08 (0.01 - 0.29) and improved after the surgery to 0.38 ± 0.26 (0.00 - 1.00), the improvement being statistically significant (p=0.000). ConclusionRetrobulbar anesthesia is an effective and safe method in macular hole surgery. Macular hole surgery can be done well under local anesthesia, and visual acuity improved significantly.